2023
DOI: 10.1371/journal.pone.0282057
|View full text |Cite
|
Sign up to set email alerts
|

Effect of photodynamic therapy on choroid of the medial area from optic disc in patients with central serous chorioretinopathy

Abstract: Purpose To explore the effect of photodynamic therapy (PDT) on the choroid of medial area from optic disc and factors correlated with treatment outcomes, we evaluated choroidal changes using ultra-widefield optical coherence tomography (UWF-OCT) after PDT for central serous chorioretinopathy (CSC). Methods In this retrospective case-series, we included CSC patients who received a standard-dose of full-fluence PDT. UWF-OCT were examined at baseline and 3 months after treatment. We measured choroidal thickness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Furthermore, PDT is the most effective treatment for central serous chorioretinopathy, one of the representative diseases of pachychoroid-spectrum disorders [ 38 ]. The choroidal blood flow overload is indicated as a crucial pathogenetic factor in pachychoroid-spectrum disorders [ 39 , 40 ], and PDT is suggested to alleviate stasis throughout the choroid, extending beyond the irradiated areas [ 41 ]. These findings correspond with the higher observed efficacy of PDT in treating PCV with a pachychoroid phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, PDT is the most effective treatment for central serous chorioretinopathy, one of the representative diseases of pachychoroid-spectrum disorders [ 38 ]. The choroidal blood flow overload is indicated as a crucial pathogenetic factor in pachychoroid-spectrum disorders [ 39 , 40 ], and PDT is suggested to alleviate stasis throughout the choroid, extending beyond the irradiated areas [ 41 ]. These findings correspond with the higher observed efficacy of PDT in treating PCV with a pachychoroid phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, cases that did not require additional treatment were significantly older than those that required further treatment. Previous reports have indicated that PDT can decrease choroidal blood flow, potentially alleviating choroidal vascular stasis [ 41 , 42 ]. Furthermore, choroidal blood flow has been reported to decline with increasing age [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…While we acknowledge that our method may not be flawless, we propose it as a novel approach to measuring peripheral choroidal thickness. 1,6,7 The observations raised by Mignone et al are valuable, and we are keen to maintain a constructive dialog on these matters. The critical issue of compensating for ocular axial length in measurements warrants ongoing consideration.…”
mentioning
confidence: 95%
“…The study we have published used these methods to produce a widefield choroidal thickness map. 1,6,7…”
mentioning
confidence: 99%
See 1 more Smart Citation